Systems thinking to understand the complexity of antimicrobial resistance across One Health: A systematic review of current approaches - Yen Pham; Teresa M. Wozniak (One Health)
Antimicrobial resistance (AMR) is a significant global threat that affects not only human health but also the health of animals and the environment. The evolution and spread of AMR are driven by a complex set of interconnected factors across all domains of One Health. Effectively addressing this challenge requires systems approaches and collaborative efforts across multiple sectors. We conducted a systematic quantitative literature review to explore the application of systems thinking approaches in examining the factors driving AMR and their interactions across human, animal and environmental systems. Based on 21 selected studies, we developed a causal loop diagram to illustrate key contributing factors and their interrelationships influencing AMR and highlight the need for interventions that extend beyond antibiotic use. Our findings emphasise that reducing antibiotic use in a single system is insufficient to curb AMR. Instead, sustained reductions require a multifaceted approach, including stronger regulations, increased awareness of appropriate antibiotic prescribing and use, non-antimicrobial measures such as vaccination and infection control, and improved waste and wastewater treatment practices. Despite progress in understanding AMR, critical gaps remain in assessing how social determinants, human activities, and environmental factors contribute to its evolution and spread. Systems thinking has proven valuable in fostering a shared understanding of AMR, facilitating collaborative decision-making, and informing evidence-based policies. Engaging stakeholders in co-designing and evaluating interventions will be essential to advancing global efforts to mitigate AMR and achieve long-term, sustainable solutions.